Tinjauan Yuridis Poligami Tanpa Izin dalam Hukum Perkawinan: Studi Kasus Ahmad Dhani dan Maia Estianty - Karenina Fernandya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Marriage is one of the fundamental institutions in Indonesian law, regulated through Law Number 1 of 1974 concerning Marriage as subsequently amended by Law Number 16 of 2019. The practice of polygamy in Indonesia is not absolutely prohibited, yet it is subject to strict requirements, including obtaining prior permission from the Religious Court and consent from the existing wife or wives. The absence of such permission constitutes a serious violation of marital law. This study examines the juridical review of polygamy without permission under Indonesian marriage law, focusing on the high-profile case of Ahmad Dhani and Maia Estianty. Using a normative legal research method with a statutory and case study approach, this paper analyzes the legal basis of polygamy regulation, the legal consequences of unauthorized polygamy, and the legal remedies available to aggrieved parties. The findings indicate that Ahmad Dhani's marriage to Mulan Jameela without obtaining permission from the Religious Court and without the consent of his first wife, Maia Estianty, constituted an unlawful act under Indonesian marriage law. Such unauthorized polygamy renders the second marriage legally defective and potentially voidable. Furthermore, the aggrieved wife has the legal right to file for divorce and claim compensation under applicable civil law provisions. This study also reveals systemic weaknesses in the enforcement of polygamy regulations in Indonesia, particularly the lack of effective sanctions against violators. Recommendations are directed at legislative reform to strengthen existing provisions and enhance judicial oversight of polygamous marriages in Indonesia.